2021
DOI: 10.3390/nu13093290
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Predicts Healthy Late-Life Aging in Male Mice

Abstract: Calorie restriction (CR) extends lifespan and retards age-related chronic diseases in most species. There is growing evidence that the gut microbiota has a pivotal role in host health and age-related pathological conditions. Yet, it is still unclear how CR and the gut microbiota are related to healthy aging. Here, we report findings from a small longitudinal study of male C57BL/6 mice maintained on either ad libitum or mild (15%) CR diets from 21 months of age and tracked until natural death. We demonstrate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Regarding the correlation of certain biomarkers with gut microbiota, Ke et al (2021) revealed that some hematological parameters that were significantly increased in aged miceincluding mean corpuscular volume, neutrophil to lymphocyte ratio, and lymphocytewere correlated to some gut microbes . In the study of Maffei et al (2017), the Frailty Index (FI 34 ) was found to be positively correlated with the abundance of Coprobacillus and Dialister and negatively correlated to Paraprevotella, Sutterella, and Rikenellaceae family OTU .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the correlation of certain biomarkers with gut microbiota, Ke et al (2021) revealed that some hematological parameters that were significantly increased in aged miceincluding mean corpuscular volume, neutrophil to lymphocyte ratio, and lymphocytewere correlated to some gut microbes . In the study of Maffei et al (2017), the Frailty Index (FI 34 ) was found to be positively correlated with the abundance of Coprobacillus and Dialister and negatively correlated to Paraprevotella, Sutterella, and Rikenellaceae family OTU .…”
Section: Discussionmentioning
confidence: 99%
“…Biological aging is thus argued as a more comprehensive and reliable predictor of the deleterious effects of aging as well as the development of mitigating therapies [ 78 , 79 ]. In this regard, there is some evidence that decreased gut microbial diversity may be correlated with the “frailty index” which is considered a predictor of the biological age and healthspan [ 80 , 81 ]. However, the relationship between gut dysbiosis and longevity is relatively well studied.…”
Section: Gut Microbiota In Aging and Associated Diseasesmentioning
confidence: 99%
“…Gut microbial features can be used to predict healthy aging or mortality in elderly individuals. 7 , 8 Interestingly, experiments on mice demonstrated that transplantation of aged donor microbiota accelerates specific processes of age-associated brain degeneration in the recipient, and conversely, transplantation of young donor microbiota can reverse this condition. 9 , 10 It has been suggested that the gut microbiota could serve as a potential therapeutic target for new anti-aging interventions.…”
Section: Introductionmentioning
confidence: 99%